Evaluation of Location of Canalis Sinuosus in the Maxilla Using Cone Beam Computed Tomography - Şalli Gülay Altan; Öztürkmen Zeynep (Balkan Stomatological Society, 2021)
Background/Aim: The aim of this study is to evaluate the prevalence of a canalis sinuosus (CS) in the anterior maxilla.